Boruto. Two blue vortex. 2 - Kishimoto, Masashi, 1974- (Shonen Jump manga., 2025)
"Naruto was a young shinobi with an incorrigible knack for mischief. He achieved his dream to become the greatest ninja in his village, and now his face sits atop the Hokage monument. But this is not his story ... The next generation of ninja stands in the swirling vortex of a new ninja age, with Naruto's own son, Boruto, at the center! It's been three years since the event that caused Boruto and Kawaki to switch places in the ninja world. As Boruto trains with Sasuke, the Ten-Tails undergoes a terrifying transformation into Divine Tree beings that each have their own consciousness. These new threats against the world must be stopped, but Boruto will first need to survive the ninja of his own village who now see him as the enemy"--Provided by publisher